The Use of Scaffolding in Physics Learning: A Systematic Review - Kurniawan, Lilik; Kuswanto, Heru; Dwandaru, Wipsar Sunu Brams (STKIP Singkawang, 2024)
The scaffolding strategy has been researched in 17 countries around the world regarding its effectiveness in helping improve students' competence in learning. This strategy is implemented directly with the learning model and integrated into physics learning media. The purpose of this study is to provide a description of research trends, methods, and findings on the use of scaffolding in the physics learning process. Systematic Literature Review (SLR) is the method of this research. Article data in the last 6 years (2018–2023) was collected from the Scopus database with the help of the Publish or Perish (PoP) 7 program and the Science Direct database. There were 52 articles selected using the PRISMA technique. Future research has the opportunity to develop learning media that contain scaffolding strategies to support a meaningful physics learning process. The focus of future research can lead to increased learner independence and 21st century skills through scaffolding strategies implemented in various forms of learning media development.